Does awareness of penalties influence deterrence mechanisms? A study of young drivers' awareness and perceptions of the punishment applying to illegal phone use while driving. (April 2021) - Truelove, V.; Freeman, J.; Mills, L.; Kaye, S.-A.; Watson, B.; Davey, J.
Highlights: Greater awareness of phone use while driving penalty is required. More participants underestimate, as opposed to overestimate, the phone penalty. Young driver hands-free phone penalty is considered too high. Hand-held phone penalty is considered reasonable. Acceptance of phone penalty linked to perceived legitimacy of the rule. Abstract: This research implemented both qualitative and quantitative methods to 1) explore young drivers' (aged between 17 and 25 years) awareness and perceptions of legal sanctions associated with phone use while driving and 2) identify whether the accuracy of their knowledge influences deterrence-related perceptions. In the qualitative phase, 60 Queensland motorists participated in focus groups. The findings of the focus groups highlighted that greater awareness of the penalty for phone use while driving would enable this punishment to act as a more salient deterrent. More specifically, the penalty for hands-free phone use was considered too high, whereas when the penalty was applied to hand-held phone use it was considered reasonable, with some commenting that increasing the fine could be a greater deterrent. However, the penalty also appeared to be linked to the perceived legitimacy of the rule. The quantitative phase utilised a cross-sectioanl survey design and consisted of 503 drivers. Overall, more participants appear to be underestimating (63% underestimated the fine and 37% underestimated the demerit points) as opposed to overestimating (14% overestimated the fine and 22% overestimated the demerit points) the penalty for phone use while driving. As expected, compared to those who accurately estimated the extent of the punishment (both the monetary sanction and the number of demerit points) associated with phone use while driving, drivers who underestimated the phone punishment (points and fine) had significantly lower perceptions of the severity of punishment. These findings suggest that some young drivers do not have sufficient knowledge of mobile phone sanctions, which has significant implications for ongoing attempts to maximise deterrent mechanisms.